Kafirin biofilm quality : effect of sorghum variety and milling fractions - Taylor, J.R.N. (John Reginald Nuttall) (University of Pretoria, 2013)
Dissertation (MSc (Agric) Food Sience and Technology)--University of Pretoria, 2005.